1999
DOI: 10.1161/01.hyp.33.4.987
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Baroreflex Control of the Sinus Node During Dobutamine Exercise Stress Testing

Abstract: Abstract-The contributions of increases in circulating catecholamines, changes in central command, and muscle afferents on baroreflex control of the sinus node during exercise are unclear. We used a dobutamine infusion to induce hemodynamic changes comparable to those of moderate physical exercise in the absence of changes in central command and muscle afferents in 13 healthy subjects. Dobutamine (up to 9 g/kg body weight per minute) increased systolic blood pressure, shortened the RR interval, increased systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We have previously reported that GDT in the same trial is associated with reduced cardiac (vagal) parasympathetic activity, as revealed by changes in heart rate variability and despite similar heart rates between groups [13]. A similar observation in reduced cardiac (vagal) parasympathetic activity has been described during stress echocardiography [36, 37]. Furthermore, we have also shown in separate cohorts of patients that impaired baroreflex dysfunction—which is in part characterized by reduced parasympathetic tone—is also associated with excess morbidity [38, 39].…”
Section: Discussionsupporting
confidence: 54%
“…We have previously reported that GDT in the same trial is associated with reduced cardiac (vagal) parasympathetic activity, as revealed by changes in heart rate variability and despite similar heart rates between groups [13]. A similar observation in reduced cardiac (vagal) parasympathetic activity has been described during stress echocardiography [36, 37]. Furthermore, we have also shown in separate cohorts of patients that impaired baroreflex dysfunction—which is in part characterized by reduced parasympathetic tone—is also associated with excess morbidity [38, 39].…”
Section: Discussionsupporting
confidence: 54%
“…These findings contrast with our study where large and sustained hemodynamic improvements with dobutamine did not modify the markedly elevated sympathetic activity in patients with severe CHF. Dobutamine does not improve baroreflex sensitivity (19,31). Our study, therefore, emphasizes the importance of arterial baroreflex activation on sympathetic nerve inhibition during pharmacologic interventions that do not improve arterial baroreflex function (19,22,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 64%
“…Dobutamine does not improve baroreflex sensitivity (19,31). Our study, therefore, emphasizes the importance of arterial baroreflex activation on sympathetic nerve inhibition during pharmacologic interventions that do not improve arterial baroreflex function (19,22,(31)(32)(33). Limited hemodynamic improvements during short-term dobutamine infusion did not improve sympathetic activity in CHF patients (20).…”
Section: Discussionmentioning
confidence: 70%
“…Dobutamine is known to increase HR and BP artificially and also to blunt baroreceptor function (van de Borne et al 1999; Zaza and Lombardi 2001), which normally would elicit a vagal reflex when BP increases. Van de Borne et al (1999) found that the largest decreases in baroreflex sensitivity (BRS) occurred during the largest increases in BP induced by dobutamine.…”
Section: Discussionmentioning
confidence: 99%